Analisis Gender Penyadap Pinus di Dusun Sidomulyo, RPH Gunungsari, KPH Banyuwangi Barat, Jawa Timur - Pratiwi Pratiwi; Agus Purwoko; Junjungan Junjungan (Peronema Forestry Science Journal, 2015)
One of the efforts made in the implementation of community based forest management is to empower communities around the forest to do pine tapping, the community involved not only men, in the era of emancipation, women can also be involved. The purpose of this study was to determine the roles of women and men in pine tapping and in making decisions associated with the pine tapping, as well as to determine the contribution of pine tapping on household income. From the aspect of working time, the role of men is greater than women in pine tapping activities, the working time of men at 39,61 hours/week and women at 9,07 hours/week. Decision-making in the family and productive activities conducted by men, issues concerning the domestic interests or reproductive dominated by women, while the financial conducted together. Respondents’ income contribution from pine tapping amounted to 73.23% from total household income.Keywords : gender, pine tappers, household income, RPH Gunungsari